Penerapan ‘Khimar Iqab’ Sebagai Simbolisasi Hukuman Dalam Membentuk Kontrol Sosial di Lingkungan Asrama - Tatsbita Hasna Luthfiana (Universitas Sebelas Maret (UNS), 2025)
Boarding school is a religious-based educational institution that combines the values of madrasah and pesantren, to develop character and discipline through the application of structured rules. Despite getting full supervision from the administrators and ustadzah, violations are still committed so that there is punishment (iqab) as an effort to realize social control. One form of iqab carried out in Hadil Iman Girls' Dormitory is 'khimar iqab', which is a form of punishment for serious offenses. This study aims to explore the effectiveness of the khimar iqab mechanism as social control in shaping the behavior of santriwati in accordance with the norms and values adopted in the dormitory. The research was studied with 4 elements of Travis Hirschi's thinking in Social Control Theory. Research data were obtained using a qualitative method with a case study approach through in-depth interviews with coaches, administrators, and santriwati in the dormitory. The results showed that the mechanism for implementing khimar iqab was not effective enough to be applied in giving the effect of shame. However, this punishment is still a form of punishment that is avoided, gets attention, and is seen as unfavorable in the dormitory environment. Therefore, khimar iqab has an active role in shaping social control in the dormitory environment.Kata Kunci: santriwati, aturan, khimar iqab, kontrol sosial